Opto-acoustic thin-film transducers for imaging of Brillouin oscillations on living cells - Perez Cota, Fernando (2016)
In any given media, the speed of sound is considerably slower than speed of light, and the exploration of the acoustic regime in the GHz range gives access to very short acoustic wavelengths. Short acoustic wavelengths is an intriguing path for high resolution live-cell imaging. At low frequencies, ultrasound has proved to be a valuable tool for the mechanical characterisation and imaging of biological tissues. There is much interest in using high frequency ultrasound to investigate single cells due to its mechanical contrast mechanism. Mechanical characterisation of cells has been performed by a number of techniques, such as atomic force microscopy, acoustic microscopy or Brillouin microscopy. Recently, Brillouin oscillations measurements on vegetal and mammal cells have been demonstrated in the GHz range. In this thesis, a method to extend this technique, from the previously reported single point measurements and line scans, into a high resolution acoustic imaging tool is presented. A novel approach based around a three-layered metal-dielectric-metal film is used as a transducer to launch acoustic waves into the cell being studied. The design of this transducer and imaging system is optimised to overcome the vulnerability of a cell to the exposure of laser light and heat without sacrificing the signal to noise ratio. The transducer substrate shields the cell from the laser radiation by detecting in transmission rather than reflection. It also generates acoustic waves efficiently by a careful selection of materials and wavelengths. Facilitates optical detection in transmission due to simplicity of arrangement and aids to dissipate heat away from the cell. The design of the transducers and instrumentation is discussed and Brillouin frequency images (two and three dimensions) on phantom, fixed and living cells are presented.